2014
DOI: 10.1155/2014/179415
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Topographic Model to Predict the Northern Hardwood Forest Type within Carolina Northern Flying Squirrel (Glaucomys sabrinus coloratus) Recovery Areas of the Southern Appalachians

Abstract: The northern hardwood forest type is an important habitat component for the endangered Carolina northern flying squirrel (CNFS;Glaucomys sabrinus coloratus) for den sites and corridor habitats between boreo-montane conifer patches foraging areas. Our study related terrain data to presence of northern hardwood forest type in the recovery areas of CNFS in the southern Appalachian Mountains of western North Carolina, eastern Tennessee, and southwestern Virginia. We recorded overstory species composition and terra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…We derived elevation (meters above sea level), slope (degrees), aspect (sine‐transformed) using 30‐m digital elevation models (DEM; U.S. Geological Survey 2000). We calculated a topographic exposure index (TEI), where higher TEI values indicate greater topographic exposure, using the zonal statistics tools in ArcMap, by subtracting the average elevation of a 1.75‐km 2 circular area around each camera (Evans et al , Ford et al ). We buffered each camera location based on average male winter home range estimate for the species (1.75 km 2 ; Lesmeister et al ).…”
Section: Methodsmentioning
confidence: 99%
“…We derived elevation (meters above sea level), slope (degrees), aspect (sine‐transformed) using 30‐m digital elevation models (DEM; U.S. Geological Survey 2000). We calculated a topographic exposure index (TEI), where higher TEI values indicate greater topographic exposure, using the zonal statistics tools in ArcMap, by subtracting the average elevation of a 1.75‐km 2 circular area around each camera (Evans et al , Ford et al ). We buffered each camera location based on average male winter home range estimate for the species (1.75 km 2 ; Lesmeister et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Topographic exposure was derived by subtracting the average elevation of the area within a 1-km radius surrounding a pixel from the elevation of the pixel. Relatively high TEI values indicate that sites were exposed peaks or ridges, whereas low or negative values indicate that sites were sheltered landforms such as coves, lower slopes, and stream corridors (Evans et al 2014;Ford et al 2015). Ford et al (2005) and Owen et al (2003) indicated that divisions among riparian and upland forests locally on the FEF were important predictors of bat occurrence and bat foraging habitat selection.…”
Section: Methodsmentioning
confidence: 99%